Redtape Pelayanan Publik (Studi Kasus: Pelayanan Sertifikat Tanah Di Kantor Badan Pertanahan Nasional) Di Kabupaten Enrekang - Karia, Febry Angraeni; Setiawati, Budi; Kasmad, Rulinawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This research was objected to find out the Redtape Of Public Service (Case Study : Land Certificate Service At The National Land Authority) In Enrekang.  The research used qualitative method with study case there were 7 respondents using primary and secondary data. Data were obtained through observation, interview, and documentation using data reduction, data presentation and conclusion. This reseach found that redtape of public service for land certificate in Enrekang regency is still needed to develop effective, fast, and efficient human resources in Enrekang regency. This service improvement enables sociefies to obtain their rights and hopefully facilitates such a good public service for the society.